Synthesis and characterization of three pyrazolate inner diazonium salts: green, powerful and stable primary explosives. (1st August 2017) - Du, Yao; Zhang, Jichuan; Peng, Panpan; Su, Hui; Li, Shenghua; Pang, Siping
Abstract : Three pyrazole based inner diazonium salts were synthesized with admirable performances, which can be used as potential primary explosives. Abstract : The synthesis and energetic performances of three inner diazonium salts, 3, 5-dichloro-4-diazopyrazole zwitterion (1 ), 4-diazo-3, 5-dinitropyrazole zwitterion (2 ), and 4-diazo-5-nitro-pyrazol-3-one zwitterion (3 ), were investigated in this study. All these compounds were characterized by IR, UV/Vis, 13 C and 15 N NMR spectroscopy, and elemental analysis. Their structures were further confirmed by single crystal X-ray diffraction. Moreover, their thermal stabilities are determined by differential scanning calorimetry (DSC). In addition, detonation parameters ( e.g. detonation velocity and pressure) of the target compounds were computed using EXPLO5 v6.01 based on the calculated heat of formation and density. The results show that compound2 exhibits a density of 1.849 g cm −3 and a decomposition temperature ( T d ) of 154 °C, which are superior to those of the efficient primary explosive DDNP (2-diazo-4, 6-dinitrophenol, T d = 142 °C). Compounds1 and3 also have moderately high decomposition temperatures of 135 and 151 °C, respectively. Besides, compounds2 and3 exhibit good detonation properties (2, 9038 m s −1, 35.0 GPa;3, 8055 m s −1, 26.4 GPa), which are higher than those of the widely used primary explosives DDNP (7290 m s −1, 23.7 GPa) and Pb(N3 )2 (5876 m s −1, 33.4 GPa). The moderately high thermal stabilities combined with the good detonation properties make them potential green primary explosives.